Quantifying modern biomes based on surface pollen data in China - Chen, Yu; Ni, Jian; Herzschuh, Ulrike (Global and planetary change, 2010)
Large-scale surface pollen records and reconstructions of modern biomes are a necessary prerequisite for the understanding of past vegetation and climate changes, especially in large countries such as China which is subject to a variety of climatic regimes and has experienced long-term intensive anthropogenic disturbances. An updated surface pollen data set consisting of 2324 samples and 737 taxa is used to reconstruct biome distribution in China according to a newly established and well-tested global classification of plant functional types, based on the regional assessment of pollen taxa and the quantitative pollen-biome assignment method of biomization. Nineteen reconstructed types of biome present a reasonable reflection of the latitudinal and altitudinal distributions of modern vegetation in China. Incorrect assignment has previously occurred in some biomes, for example among the cold and cool temperate coniferous forests and mixed forest, among warm-temperate evergreen forest, mixed forest and tropical forests, and among temperate shrubland, grassland, desert and tundra biomes. Mega-biomes, grouped for the same bioclimatic zones, result in a better reconstruction than the nineteen separate biome types. The correct assignments increased from 68.8% to 80.6%. However, comparison of pollen-based biome reconstructions to climate-driven vegetation simulations performed using the global vegetation model BIOME4 indicates a low correlation rate (only 24.8%), suggesting that more needs to be done to combine palaeoenvironmental data with model simulations of past vegetation changes. The misassignment of surface pollen to modern biomes usually occurs in areas which have similar bioclimatic features and vegetation types and for biomes which share the same plant functional types. These mis-matches often occur in mountainous regions where transitional vegetation zones occur on hill slopes at mid-altitudes. Our new modern biome reconstruction for China is more robust and reliable; however continued analysis of pollen records is required in the remote areas of western China and the Tibetan Plateau, as well as in regions of central and eastern China which have suffered from high levels of anthropogenic activity. This type of anthropogenic biome reconstruction presents a new challenge.